Expatriates recruitment and selection for long-term international assignments in portuguese companies - Martins, Dora (2015)
Long-term international assignments’ increase requires more attention being paid for the preparation of these foreign assignments, especially on the recruitment and selection process of expatriates. This article explores how the recruitment and selection process of expatriates is developed in Portuguese companies, examining the main criteria on recruitment and selection of expatriates’ decision to send international assignments. The paper is based on qualitative case studies of companies located in Portugal. The data were collected through semi-structured interviews of 42 expatriates and 18 organisational representatives as well from nine Portuguese companies. The findings show that the most important criteria are: (1) trust from managers, (2) years in service, (3) previous technical and language competences, (4) organisational knowledge and, (5) availability. Based on the findings, the article discusses in detail the main theoretical and managerial implications. Suggestions for further research are also presented.